The CogniAid trial. The impact of two hearing aid signal processing strategies on cognition - Searchfield, Grant Donald; McAuliffe, Megan J.; Fok, Christine; Kyaw, Tin Aung; Williams, Eric; Burton-Harris, Lisa; Coad, Gavin; Grady, Jonny; Smith, Alice; Vajsakovic, Dunja (Frontiers in Audiology and Otology, 2024)
Background: Untreated hearing loss is a risk-factor for age-related cognitive decline and hearing aids have been shown to slow cognitive decline in a population at risk for dementia. This double-blind multiple site randomized trial tested the hypothesis that for older adults with below-average cognition a "Simple" hearing aid fitting strategy (based on linear amplification with output limiting compression signal processing) would improve hearing and cognition more than a "Standard" approach (adaptive compression-based processing). Methods: Two-hundred and fifty-six adults aged over 65 were screened for cognitive function using the NIH toolbox cognitive battery. Participants with below median age-adjusted fluid composite cognitive scores (<100) were eligible to participate (n=104).Sixty-seven eligible participants proceeded to trial and were randomized 1:1 to a simple or standard hearing aid fitting. Participants in the Standard group were fitted with hearing aids matched to nonlinear real-ear prescription targets (either NAL-NL1 or NL2) while participants in the Simple group were fitted with hearing aids matched to linear prescription targets (NAL-R). Participants and researchers not fitting the hearing aids were blinded to allocation. Results: Forty-eight participants completed assessments to 12 months. The Standard hearing aid group improved on measures of fluid cognition and hearing. There was a statistically significant difference in fluid cognition scores between groups. The fluid cognition composite score for participants receiving the Simple fitting changed by 3.5 points. Those with the Standard fitting improved by 10.3 points. Hearing outcomes for each group where improved by the same amount. Conclusion: This is the first study to show that hearing aid fitting strategies using markedly different signal processing result in significantly different cognitive outcomes after 12 months of use. The Standard fitting resulted in greater improvement in cognition than the Simpler fitting which was the opposite result to what had been hypothesized. The results reinforce findings indicating hearing aid benefits for the elderly and that they improve cognition.